2000
DOI: 10.1175/1520-0477(2000)081<2563:asgpso>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

ARM Southern Great Plains Site Observations of the Smoke Pall Associated with the 1998 Central American Fires

Abstract: Drought-stricken areas of Central America and Mexico were victimized in 1998 by forest and brush fires that burned out of control during much of the first half of the year. Wind currents at various times during the episode helped transport smoke from these fires over the Gulf of Mexico and into portions of the United States. Visibilities were greatly reduced during favorable flow periods from New Mexico to south Florida and northward to Wisconsin as a result of this smoke and haze. In response to the reduced v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 48 publications
(39 reference statements)
1
47
0
Order By: Relevance
“…Figure 1 shows the resulting annual OC emissions from biomass burning in North and Central America for 1997-2000 as well as the climatological mean. An ENSO-related drought resulted in catastrophic wildfires in the tropical forests of southern Mexico and Central America in 1998 [Peppler et al, 2000]. Canadian fire emissions were also unusually large in 1998.…”
Section: Generalmentioning
confidence: 99%
“…Figure 1 shows the resulting annual OC emissions from biomass burning in North and Central America for 1997-2000 as well as the climatological mean. An ENSO-related drought resulted in catastrophic wildfires in the tropical forests of southern Mexico and Central America in 1998 [Peppler et al, 2000]. Canadian fire emissions were also unusually large in 1998.…”
Section: Generalmentioning
confidence: 99%
“…Effects of large wildfires in Northwestern Canada have been observed on air pollutant concentrations in Tennessee, 21 and transport and impact of smoke from wildfires and biomass burning in Southern Mexico and Central America have been observed in the central and southeastern portions of the United States. 22,23 The contributions of natural fires to background carbon concentrations have just begun to be quantified. They are, of course, highly episodic at any given location.…”
Section: Carbon From Wildfiresmentioning
confidence: 99%
“…This relative humidity control minimizes the effects of changing relative humidity on the measurements and provides a reference point where the properties of ambient aerosols are measured. Bergin et al (1997) and Peppler et al (2000) reported that losses of ammonium nitrate (and less volatile species) due to evaporation under the sampling conditions used in ARM aerosol observing system are small. Size-segregated measurements of σ s and σ a were made through a switch impactor system, such that only particles with aerodynamic diameter D p smaller than 10 µm were sampled.…”
Section: Aerosol Measurements: Optical Properties and Number Concentrmentioning
confidence: 99%
“…Lowest K + concentrations are recorded in winter. Although local field burning occurs in the vicinity of the SGP many times in the year, these activities are most pronounced in May, June and July (Peppler et al, 2000;Iziomon and Lohmann, 2003). Wind blown soil dust contains a significant amount of Ca, Mg, Al, Fe, Ti and Si (Barie and Barrie 1990, Malm et al 1996.…”
Section: Seasonal Variation Of Aerosol Number Concentration Chemicalmentioning
confidence: 99%